2019
DOI: 10.15713/ins.jcri.267
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in an orthodontic perspective

Abstract: Genetics is the science concerned with the structure and function of all genes in different organisms. Malocclusion is a manifestation of genetic and environmental interaction on the development of the orofacial region. It is important to consider genetic factors to understand the cause of existing problems, which has influence the outcome of treatment.The review aims to provide information to the dental practitioner and orthodontist on basics of genetics and common disorders with gene impairments. These genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This will allow objective generation of three-dimensional models for advanced diagnosis and treatment planning whilst saving the time and efforts required for manual segmentation. 64 Growth and development of orofacial complex are influenced by the interaction of the genetic and environmental factors.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This will allow objective generation of three-dimensional models for advanced diagnosis and treatment planning whilst saving the time and efforts required for manual segmentation. 64 Growth and development of orofacial complex are influenced by the interaction of the genetic and environmental factors.…”
Section: Data Processingmentioning
confidence: 99%
“…Furthermore, various methods for automatic volumetric segmentation of CBCT images were developed using ML algorithms. This will allow objective generation of three‐dimensional models for advanced diagnosis and treatment planning whilst saving the time and efforts required for manual segmentation 64 …”
Section: Development Of Clinical Decision Support Systems (Cdsss)mentioning
confidence: 99%
“…MSX1, MSX2, HOX, distal-less genes, OTX, goosecoid gene and PTHR are some of the genes that plays a key role in the craniofacial development. 1 An attractive or pleasing smile clearly enhances the acceptance of an individual in our society by improving the initial impression in interpersonal relationships. Differently from what some orthodontists consider, smile harmony is determined not only by the shape, position and color of teeth, but also by the gingival tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In 1836, Frederick Kussel reported that malocclusion, both skeletal and dental, could be transmitted from one generation to another and also stated that chromosomal defects account for approximately 10% of all malocclusions. 1 The pioneering work of Gregor Johann Mendel initiated an interest in the field of genetics in the 19th century, and since then, genetics has been an essential part of the studies performed in various fields of biological and medical sciences. Since the 20th century, this branch of science has evolved through a series of era-based conceptual breakthroughs.…”
Section: Introductionmentioning
confidence: 99%